2011
DOI: 10.1128/jvi.06048-11
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Inactivated Severe Acute Respiratory Syndrome Coronavirus Vaccine Provides Incomplete Protection in Mice and Induces Increased Eosinophilic Proinflammatory Pulmonary Response upon Challenge

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV) is an important emerging virus that is highly pathogenic in aged populations and is maintained with great diversity in zoonotic reservoirs. While a variety of vaccine platforms have shown efficacy in young-animal models and against homologous viral strains, vaccine efficacy has not been thoroughly evaluated using highly pathogenic variants that replicate the acute end stage lung disease phenotypes seen during the human epidemic. Using an adjuvanted and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
499
4
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(563 citation statements)
references
References 68 publications
38
499
4
9
Order By: Relevance
“…However, an early concern for application of a SARS-CoV vaccine was the experience with animal coronavirus vaccines, which induced enhanced disease and immunopathology in animals when challenged with infectious virus [96]. Indeed, a similar immunopathologic reaction has been described in mice vaccinated with a SARS-CoV vaccine and subsequently challenged with SARS-CoV [97,98,99,100,101]. Thus, safety concerns related to effectiveness and safety for vaccinated persons, especially if exposed to other coronaviruses, should be carefully examined.…”
Section: Epidemiology and Impact Of Coronaviruses In Human Healthmentioning
confidence: 99%
“…However, an early concern for application of a SARS-CoV vaccine was the experience with animal coronavirus vaccines, which induced enhanced disease and immunopathology in animals when challenged with infectious virus [96]. Indeed, a similar immunopathologic reaction has been described in mice vaccinated with a SARS-CoV vaccine and subsequently challenged with SARS-CoV [97,98,99,100,101]. Thus, safety concerns related to effectiveness and safety for vaccinated persons, especially if exposed to other coronaviruses, should be carefully examined.…”
Section: Epidemiology and Impact Of Coronaviruses In Human Healthmentioning
confidence: 99%
“…Subunit vaccines are more appealing because it was found that the inactivated whole SARS‐CoV used as a vaccine resulted in enhanced lung immunopathology when vaccinated animals were challenged with SARS‐CoV . This was attributed to the presence of N‐specific antibodies rather than S‐specific antibodies; therefore, using the whole S antigen in a vaccine could be as safe as using minimum RBD.…”
Section: Current Mers‐cov Vaccine Candidates Under Developmentmentioning
confidence: 99%
“…Similarly, laboratory animals administered alum-adjuvanted whole-virus SARS-CoV vaccine and subsequently challenged with infectious virus experienced enhanced disease and immunopathology comprised of eosiniophilic infiltration and Th2-mediated inflammatory alveolar damage [21], similar to immunopathologic lung reactions found in infants and animals challenged with respiratory syncytial virus (RSV) [22,23]. A double-inactivated SARS-CoV (formalin and ultraviolet radiation) was also shown to elicit eosinophilic and immunoenhancing pathology, as well as poor protection, especially in aged animals, suggesting the possibility that aged humans (a desired target population for the vaccine) may be particularly vulnerable to vaccine-induced effects [24]. Further studies showed that a Venezuelan equine encephalitis vector containing the SARS nucleocapsid (NP) gene also elicited eosinophilic immunopathology in BALB/c mice after challenge without any noticeable protection [25].…”
Section: Comparative Advantage Of An Rbd-s Sars Vaccinementioning
confidence: 99%